A Facile Method for Generating a Smooth and Tubular Vessel Lumen Using a Viscous Fingering Pattern in a Microfluidic Device - Tu, Ting-Yuan; Shen, Yen-Ping; Lim, Sei-Hien; Wang, Yang-Kao (Frontiers in Bioengineering and Biotechnology, 2022)
Blood vessels are ubiquitous in the human body and play essential roles not only in the delivery of vital oxygen and nutrients but also in many disease implications and drug transportation. Although fabricating in vitro blood vessels has been greatly facilitated through various microfluidic organ-on-chip systems, most platforms that are used in the laboratories suffer from a series of laborious processes ranging from chip fabrication, optimization, and control of physiologic flows in micro-channels. These issues have thus limited the implementation of the technique to broader scientific communities that are not ready to fabricate microfluidic systems in-house. Therefore, we aimed to identify a commercially available microfluidic solution that supports user custom protocol developed for microvasculature-on-a-chip (MVOC). The custom protocol was validated to reliably form a smooth and functional blood vessel using a viscous fingering (VF) technique. Using VF technique, the unpolymerized collagen gel in the media channels was extruded by less viscous fluid through VF passive flow pumping, whereby the fluid volume at the inlet and outlet ports are different. The different diameters of hollow tubes produced by VF technique were carefully investigated by varying the ambient temperature, the pressure of the passive pump, the pre-polymerization time, and the concentration of collagen type I. Subsequently, culturing human umbilical vein endothelial cells inside the hollow structure to form blood vessels validated that the VF-created structure revealed a much greater permeability reduction than the vessel formed without VF patterns, highlighting that a more functional vessel tube can be formed in the proposed methodology. We believe the current protocol is timely and will offer new opportunities in the field of in vitro MVOC.